Mattampung: Studi Terhadap Proses Upacara Kematian di Dusun Kaccanning Desa Buntuk Karya Kecamatan Ponrang Selatan Kabupaten Luwu - St. Patimah (Rayhan Intermedia, 2018)
This study aims to find out: (1) Trust in the community of Kaccanning Hamlet, Buntu Karya Village, Ponrang Selatan District, Luwu Regency regarding the death ceremony of mattampung; (2) Knowing the meaning of the mattampung death ceremony in Kaccanning Hamlet, Buntu Karya Village, Ponrang Selatan District, Luwu Regency; (3) Knowing the social function of the mattampung death ceremony in Kaccanning Hamlet, Buntu Karya Village, Ponrang Selatan District, Luwu Regency. In this study used the type of qualitative research analyzed and written descriptively. Data collection techniques were carried out using the method of observation, interviews, and documentation by involving 11 (eleven) informants. Based on the results of the study show that: (1) Buntu Village Community The Work of Kaccanning Hamlet still believes in things that are unseen or believes that the spirits who died before the mattampung death ceremony are still around them and will disturb the peace of the living; (2) The meaning of the mattampung death ceremony is divided into two, namely religious meaning and meaning as a medium of social bonding. Religious meaning which means signifying the relationship between humans and the spirits of the deceased while for meaning as a medium of social ties means that there is a kind of moral and social obligation to carry out the final death ceremony; (3) The social function of the mattampung death ceremony is to maintain order in society.